IDENTIFICATION OF PHILOSOPHICAL ARCHITECTURE TRANSFORMATION FORM OF PASSENGER TERMINAL BUILDING OF KERTAJATI AIRPORT: COMPARISON OF VISUAL FEATURES OF MERAK BIRD (PEAFOWL) AND MERAK DANCE - Agung Setiawan; Sri Handayani; Fitriani Fitriani (Journal of Development and Integrated Engineering, 2021)
AbstractKertajati Airport in Majalengka, West Java is known to have an attractive architectural design with a characteristic expression of "Merak" which can be seen in several parts of the passenger terminal building, especially recognized on the roof and facade. Based on the publication of PT. West Java International Airport (BIJB) as a Regional Owned Enterprise (BUMD) responsible for the construction and management of Kertajati Airport, this airport design carries the concept of " Merak " which is referred to as a representation of the local icon of West Java. The purpose of this study is to identify the design ideas that underlie the architectural design concept of the Kertajati Airport terminal building so that the philosophical meaning that is transformed into the architectural form of this airport is the embodiment of the local expression of West Java Province can be confirmed. Through the identification of visual characteristics in several parts of the architecture of the passenger terminal building, it can be concluded that the architectural design of the Kertajati Airport terminal building is more likely to adopt the transformation of the body shape of the Merak bird than the Merak Dance. This can be seen from the results of the identification of the architectural form of the Terminal building on the typology of the building mass, the segmentation of the building, the shape of the roof, the details of the roof, and the part of the facade which are compared with the visual characteristics of the morphological form of the Merak and the visual characteristics of the costumes of the dancers of the Merak Dance. Keywords: Architectural Transformation, Philosophy, Kertajati Airport Terminal, Merak dance